EFFECT OF HOLDING TIME ON RAPID AUSTENITIZATION HEAT TREATMENT OF LOW CARBON STEEL IN AN EFFORT TO OBTAIN ADVANCED HIGH STRENGTH STEEL QUALITIES - Amardanta Priambudi, Djalu
The development of human civilization demands higher strength steel materials at lower prices in structural applications. Several methods to produce high-strength steel have been used, such as quenching and tempering. However, these methods have limitations in terms of mechanical properties and processing time. Recently, a rapid austenitization method has emerged that produces better mechanical properties with shorter processing times. In this study, a variation of the holding time in rapid austenitization is carried out due to its affect on the microstructure at the austenitization stage which has an impact on the final microstructure that will determine the final mechanical properties of the heat-treated steel. A series of rapid austenitization and conventional austenitization heat treatment experiments were conducted to study the effect of holding time on microstructure and mechanical properties. The rapid austenitization heat treatment was carried out at 1000 °C with a heating time of 15 seconds and various holding times of 0, 5, 15, 45, 90, and 180 seconds. Then, it was compared with conventional austenitization heat treatment with a holding time of 1800 seconds. After heat treatment, iced brine quenching was performed on both heat treatments. Then characterization was carried out using vickers microhardness, tensile testing, charpy impact testing, metallography using an optical microscope, and fractography using SEM. From the characterization results that have been carried out, the influence on the microstructure and mechanical properties are determined, and then compared with high strength steels in current standards and literature. A two-phase ferrite-martensite microstructure was obtained with a linear increasing trend of martensite which then changed to a very fine martensite microstructure at a holding time of 45 seconds and above. An increasing hardness trend was obtained and reached a maximum value of 493 HV at a holding time of 90 seconds, an increasing toughness trend was obtained with a maximum value of 90.5 J/cm2 at a holding time of 180 seconds, an increasing tensile strength trend was obtained with a maximum value of 1265 MPa at a holding time of 45 seconds, a decreasing elongation trend was obtained with a maximum value of 28.38% at a holding time of 5 seconds and a minimum value of 13.80% at a holding time of 180 seconds, and a trend of changing the fracture mechanism from brittle transgranular to ductile. It was found that the steel produced by rapid austenitization heat treatment in this study has entered the region of 3rd Gen Advanced High Strength Steel with the tensile strength range of 817 MPa to 1265 MPa and elongation range of 13.8% to 28.38%.